Kepuasan Pengunjung Ke Taman Tamadun Islam Di Terengganu Terhadap Kualiti Perkhidmatan Sebagai Pelancing Islam - Nik Nur Sakinah, Abu Bakar (Universiti Malaysia Sarawak (UNIMAS), 2016)
This research is aimed to investigate the level of satisfaction of visitors to the Islamic Civilisation Park in Terengganu on the quality of islamic tourism services . The main objective of the study was to examine the relationship between customer satisfaction and five SERVQUAL dimensions of physical evidence , reliability , responsiveness, assurance, empathy . This research uses quantitative methods by distributing questionnaires and involving respondents who comprised the Islamic Civilisation Park visitors and residents around Kuala Terenggamu. The results of study analyzed using Pearson correlation coefficient showed visitor satisfaction had a significant relationship with the independent variables. However , some recommendations need to be addressed in further development to improve the Islamic Civilisation Park as a tourism product of Islam in Malaysia.